Maximization of palm fruit planted area using a goal programming approach / Nur Jannah Md Zain and Wan Nurshazelin Wan Shahidan - Md Zain, Nur Jannah; Wan Shahidan, Wan Nurshazelin (UiTM Cawangan Perlis, 2018)
Malaysia is currently facing low production of palm fruit. The poor palm fruit output will inevitably affect the economy in Malaysia. Hence, the government related agency needs to find effective ways to increase the production of palm fruit. Factors that affect the production of palm fruit include palm tree planted area and quantity of the crop. This paper proposes the Goal Programming approach to maximize the production of palm fruit. The approach maximized the planted area for three rural areas and increases the number of palm fruit crop for three rural areas. This approach is used to find optimal solution to the low palm fruit output. The findings show that all the study objectives have been fully achieved. The proposed planted area available from the QM Windows 4.0 software can increase up to 75% from the existing planted area availability for three rural areas in Jengka, Pahang.